2016
DOI: 10.1089/aid.2015.0296
|View full text |Cite
|
Sign up to set email alerts
|

Younger Age Predicts Failure to Achieve Viral Suppression and Virologic Rebound Among HIV-1-Infected Persons in Serodiscordant Partnerships

Abstract: Background: Antiretroviral therapy (ART) markedly reduces the risk of HIV-1 transmission in serodiscordant partnerships. We previously found that younger age and higher CD4 counts were associated with delayed initiation of ART by HIV-1-infected partners in serodiscordant partnerships. Among those initiating ART, we sought to explore whether those same factors were associated with failure to achieve viral suppression. Methods: In a prospective study of HIV-1-infected persons who had a known heterosexual HIV-1-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 54 publications
4
28
3
1
Order By: Relevance
“…Previous studies have reported that the younger age is associated with poor antiretroviral adherence and viral load suppression [25][26][27]. Among factors put forward to be responsible for the unfavourable outcomes included higher CD4 count prior to HAART intervention [26] and delayed HAART initiation [27]. In contrast to our study, we observed statistically no clear pattern in the rate of viral suppression with respect to the various age groups (Tables 2 and 3).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that the younger age is associated with poor antiretroviral adherence and viral load suppression [25][26][27]. Among factors put forward to be responsible for the unfavourable outcomes included higher CD4 count prior to HAART intervention [26] and delayed HAART initiation [27]. In contrast to our study, we observed statistically no clear pattern in the rate of viral suppression with respect to the various age groups (Tables 2 and 3).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have reported that the younger age is associated with poor antiretroviral adherence and viral load suppression [25][26][27]. Among factors put forward to be responsible for the unfavourable outcomes included higher CD4 count prior to HAART intervention [26] and delayed HAART initiation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Yet the present study results do not support this, as the exclusion of children aged 3 years did not change the rates of viral non-suppression in the paediatric study group. Lower CD4 count at baseline was associated with not being suppressed at 12 months in adults, a finding consistent with other studies (Anude et al, 2013;Collaboration of Observational et al, 2008;Mujugira et al, 2016;Samuel et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Higher viral load at ART initiation was also associated with a longer time to viral suppression in studies where ART was initiated at lower CD4 cell counts. 15 Younger age has been associated with lack of viral suppression 16,17 and poor ART adherence 18,19 in previous studies. In HPTN 052, self-reported ART adherence was higher among older participants in the early ART arm, but this association was not statistically significant in multivariate analysis.…”
Section: Discussionmentioning
confidence: 84%